Adenolipoma of the thyroid gland - Gupta Anshu; Mathur S; Batra Charu; Gupta Anjali (Wolters Kluwer Medknow Publications, 2008)
Thyrolipoma or adenolipoma of the thyroid gland is defined as a thyroid adenoma containing mature fat tissue. It is a rare encapsulated lesion. A case of a 35-year-old female presenting with swelling in the neck that was diagnosed as adenolipoma is described because of its extreme rarity.